Visual Merchandising Pada UMKM KEDJORA Magelang - Ahmad Ali; Noor Laila Ramadhani; Arda Raditya Tantra; Abdul Aziz; Teguh Harso Widagdo (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Visual merchandising is an important strategy in the retail world which aims to attract customers, increase sales and strengthen a company's brand image. However, this concept also has the potential to provide wider benefits to society in general. This community service involves direct observation of visual merchandising practices at Kedjora Grosir Magelang MSMEs, as well as interviews with shop owners and the local community. The findings show that by using the right visual merchandising strategies, stores can become more environmentally friendly, promote local products, and provide education about relevant social issues. Community service through visual merchandising can provide benefits such as increasing awareness of environmental and social issues, empowering local producers, and creating an inclusive shopping environment for all levels of society. In addition, this initiative can also increase the sustainability of the local economy and create stronger relationships between stores and the surrounding community. This community service shows that visual merchandising is not just about creating aesthetically appealing displays, but also about harnessing the power of retail stores to have a positive impact on society. Therefore, the integration of community service principles in visual merchandising strategies can be a significant step in building sustainable relationships between business and society.